Role of early education in reading ability of deaf students - Bambang Udji Djoko Rianto (Paediatrica Indonesiana, 2009)
Background Reading is a very complex process which includescognitive process. Reading is initialized by visual analysis and lettertransformation into vocabulary form, word identification by lettersound mapping, words correlation, and interpretation. Deafnesscauses difficulties in acquiring language information via hearingprocess thus inhibits a successful conversation process.Objective To determine the role of early education in deaf students to reading ability.Methods A cross sectional design was performed from Septemberuntil December 2007. This study compared deaf students,younger than 6 years old, who received early education in specialeducation schools B (group I), with deaf children aged 6 years old and older who received education in special education schools B/conventional educational method (group II).Results There were 22 deaf children in group I and 24 in group II. The measured variables included age, age of school enrollment, duration of studies, degree of deafness, sex, and parental educational level. Logistic regression analysis showed that the variables which significantly contributed to reading skills were the early education and duration of study. In early education group, the children had significantly better reading ability (P=0.02; OR= 19.95; 95% CI 1.939 to 53.62), besides duration of study (P=O.Ol; OR=70.754; 95% CI 6.267 to 798.75), compared to conventional education.Conclussion Compared to those who receive education in specialeducation school B with a conventional educational method, deafstudents who receive early education in special education schoolsB have better reading ability significantly. Duration of studyalso contribute significantly to reading skill.